Accuracy evaluation of XUST's global ionospheric products. Issue 1 (1st July 2021) - Chen, Peng; Liu, Lixia; Liu, Hang; Yao, Wanqiang
Abstract: The ionosphere research team of Xi'an University of Science and Technology (XUST) has been committing to high-precision global ionospheric modeling research since 2012. The agency adopted spherical harmonic functions to generate GNSS (Global Navigation Satellite System) global ionospheric product XANG and multi-source data fusion global ionospheric product XAMG. In this essay, we take International GNSS Service (IGS) global ionospheric maps (GIMs) products as a reference to verify and analyze the accuracy of GIMs products produced by XUST in detail from three different aspects. The internal and external evaluation results of GNSS dSTEC indicate that the GIMs products of XUST are consistent with the GIMs products of other analysis centers. In contrast to the Jason-2/-3 VTEC, the STD between XANG and Jason-2 during 2016–2018 is about 2.42–3.11 TECU. The STD between XANG and Jason-3 is about 2.40–3.11 TECU, which is equivalent to that of China Academy of Sciences (CAS) and Jet Propulsion Laboratory (JPL), better than that of the Center for Orbit Determination in Europe (CODE), European Space Operations Center of European Space Agency (ESA) and Wuhan University (WHU), and slightly worse than that of Universitat Politècnica de Catalunya/IonSAT (UPC). Besides, we figure out that the accuracy of GIM products in approximately 60% of the ocean areas has been significantly improved after adding space-based data by comparing the two developed global ionospheric products. Finally, we evaluated the product performance of XUST in single-frequency precise point positioning (SF-PPP) with convergence time and positioning accuracy of standard single-frequency PPP as reference. In terms of average convergence time, the ionospheric delay processing capabilities of XANG and XAMG are comparable to other GIMs and even better than ESAG and JPLG in some regions. In terms of positioning accuracy, the positioning accuracy of XANG as an external ionospheric constraint is better than that of XAMG, and both are better than ESAG, JPLG and IGSG, and slightly worse than CASG and CODG.